2020
DOI: 10.3389/fpsyt.2020.577155
|View full text |Cite
|
Sign up to set email alerts
|

Continuous High Frequency Deep Brain Stimulation of the Rat Anterior Insula Attenuates the Relapse Post Withdrawal and Strengthens the Extinction of Morphine Seeking

Abstract: Deep brain stimulation (DBS) modulates the neuronal activity in specific brain circuits and has been recently considered as a promising intervention for refractory addiction. The insula cortex is the hub of interoception and is known to be involved in different aspects of substance use disorder. In the present study, we investigate the effects of continuous high frequency DBS in the anterior insula (AI) on drug-seeking behaviors and examined the molecular mechanisms of DBS action in morphine-addicted rats. Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 80 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…We have observed that the expression levels of the Npas4, Arc, and c-Fos genes in the AI of the VPA-exposed animals were considerably elevated as opposed to that of rats in the Saline group, which may be related to abnormal responses to neuronal activity in neural circuits [ 31 , 37 ]. Interestingly, long-term HF-DBS increased the expression of the IEGs in the AI of the saline-DBS group, and conversely reduced the expression of IEGs in the VPA-DBS group, suggesting that our DBS protocol dynamically modulated the AI neuronal activity, and this is consistent with previous studies [ 36 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have observed that the expression levels of the Npas4, Arc, and c-Fos genes in the AI of the VPA-exposed animals were considerably elevated as opposed to that of rats in the Saline group, which may be related to abnormal responses to neuronal activity in neural circuits [ 31 , 37 ]. Interestingly, long-term HF-DBS increased the expression of the IEGs in the AI of the saline-DBS group, and conversely reduced the expression of IEGs in the VPA-DBS group, suggesting that our DBS protocol dynamically modulated the AI neuronal activity, and this is consistent with previous studies [ 36 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this research, we first implanted electrodes into rats that had been subjected to valproic acid treatment to cause autism, and then we stimulated the animals thereafter. In addition, we used a novel design informed by prior research with an implantable stimulation generator, which allowed the test subjects to move and eat unrestrictedly and provide long-term chronic stimulation (effective voltage output for three months) [ 36 ]. We have observed that the expression levels of the Npas4, Arc, and c-Fos genes in the AI of the VPA-exposed animals were considerably elevated as opposed to that of rats in the Saline group, which may be related to abnormal responses to neuronal activity in neural circuits [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…show that the continuous HF-DBS applied to the bilateral anterior insula prevents the relapse of morphine place preference following withdrawal, facilitates its extinction, blocks reinstatement triggered by morphine priming, and reverses the expression of morphine-regulated proteins. [ 10 ] These findings, combined with previous research, suggest that modulating insular activity through pharmacological or other methods, such as DBS, holds promise as a potential treatment for SUD.…”
Section: Discussionmentioning
confidence: 81%
“…Further detection of insular lobe brain slices showed that high-frequency electrical stimulation can inactivate insular lobe neurons. Continuous DBS in the anterior insula can inhibit the recurrence of morphine CPP in rats and promote its regression (65). In a study, in which DBS targeted regions ranging from the lateral orbitofrontal cortex to the dorsal portion of the agranular insula, showed that high-frequency DBS blocks the acquisition of morphine preference, promotes extinction of morphine preference, and prevents drug-induced morphine igniting (66).…”
Section: Insula: Neuromodulatory Target For Drug Addictionmentioning
confidence: 99%